Karakteristik Produksi Cacing Tanah (Lumbricus rubellus) dengan Pakan Limbah Pasar Berupa Sayur Sawi Hijau dan Pepaya (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Environmental pollution can be minimized by utilizing traditional market waste through the cultivation of earthworms. Market waste that is commonly found is vegetable and fruit waste. Market waste that is used as feed can minimize the production budget in worm farming. This research used a completely randomized method, four treatments and three replications. The aim of this study was to investigate the effect of feed with mustard green waste and papaya waste on the productivities (body weight and body length) of Lumbricus rubellus, vermicompost production, and that economic value. The results of the study stated that the treatment significantly (P